PERAN MOTIVASI SEBAGAI VARIABEL MEDIASI PADA PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN KOPERASI DI KABUPATEN BADUNG - Anak Agung Gde Alit Wiradyatmika (Jurnal Ilmiah Satyagraha, 2022)
In managing operatives it will require very capable human resources to enable operatives to be able to bring real benefits to the economy. The purpose of this study was to determine the effect of the quality of human resources on employee performance. And knowing the role of motivation on the influence of the quality of human resources on employee performance. This study involved a sample of 65 respondents using proportional sampling. The data analysis technique used SEM-PLS. The results showed that the quality of human resources had a positive and significant effect on employee performance. And motivation can mediate the influence of the quality of human resources on employee performance.